DESIGN OF AUTOMATIC GENERATOR START SYSTEM PORTABLE ONE PHASE BASED PLC - Bustamin, Bustamin. B (Department of Electrical Engineering, University of Patria Artha, 2018)
Programmable Logic Controller (PLC) is basically a computer that contains a specific control functions of different types and levels of complexity, are used to automate the control system on the machines or processes. PLC can be programmed, controlled, and in opersikan even by one who is not so proficient in the operation of the computer. The characters are controlled by the PLC process itself is a process which is a gradual process, i.e. it goes sort to achieve final conditions expected. In this final task, one phase generator and simulation of PLC used to automatically start generator single phase designed and simulated, includes ways to the needs of the PLC programming control, and the creation of the program in the form of a ladder diagram the module is then transferred to the PLC to run commands correspond to settings that have already been designed. The system works automatically when the supply of electricity from the State electricity company cut off, then the PLC gets a signal to run the genset. If this is the case then the system will automatically start the active time starter set on the program, until the burden of getting the supply of electricity.